2004
DOI: 10.1111/j.1365-3040.2004.01260.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity, carbon isotope discrimination and leaf traits of trees of Eucalyptus globulus Labill. in relation to water availability

Abstract: D is influenced by mesophyll conductance. It is concluded that canopy conductance is a more important determinant of growth in water-limited conditions than either leaf area index or leaf traits in fertilized stands of E. globulus . Water availability was dictated more by rainfall than soil type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 59 publications
3
33
1
Order By: Relevance
“…The model predictions generally integrate previous knowledge from the literature, indicating that: 1) in water-limited conditions, water availability has greater effects on NPP than N mass (Macfarlane et al 2004, Klein et al 2005), leading to a negative correlation between NPP and d 13 C (Condon et al 1987, Roux et al 1996; and 2) when water is not limiting, NPP increases with increasing N mass (Field and Mooney 1986, Wright et al 1988, Sun et al 1996, Livingston et al 1998). Equation 5 further suggests a threshold of water limitation of E/E m B0.85.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The model predictions generally integrate previous knowledge from the literature, indicating that: 1) in water-limited conditions, water availability has greater effects on NPP than N mass (Macfarlane et al 2004, Klein et al 2005), leading to a negative correlation between NPP and d 13 C (Condon et al 1987, Roux et al 1996; and 2) when water is not limiting, NPP increases with increasing N mass (Field and Mooney 1986, Wright et al 1988, Sun et al 1996, Livingston et al 1998). Equation 5 further suggests a threshold of water limitation of E/E m B0.85.…”
Section: Discussionsupporting
confidence: 67%
“…Although the d 13 C of tree-ring and leaf materials has been considered as a reasonable indicator of integrated leaf gasexchange properties (Macfarlane et al 2004, Klein et al 2005, there are very few data to indicate the relationship between foliar d 13 C and NPP at larger geographical scales. This study is a step forward in attempts to quantitatively describe the relationships among community characteristics, climatic factors and leaf traits.…”
Section: Discussionmentioning
confidence: 99%
“…Gingko biloba trees, in Japan, also had higher D at the wettest site than the trees growing at the more arid site (Sun et al 2003). In SW Australia, and across a gradient of rainfall of 600-1,400 mm year -1 , Eucalyptus globulus leaf D ranged from 17 to 21%, and was strongly, positively correlated with the ratio of mean annual rainfall to potential evaporation (Macfarlane et al 2004). For the Mediterranean species Q. ilex, Damesin et al (1997) reported that the site with the lowest rainfall had the smaller mean value of D, whereas the greater mean value of foliar D was found at the most mesic site.…”
Section: Discussionmentioning
confidence: 94%
“…intended for bioenergy have been established mostly in Australia, New Zealand, China, South America, the Mediterranean, and Africa (Niemistö, 1995;Sochacki et al, 2007). Species of this genus are characterized by rapid growth and high wood production, making them the primary choice for biomass production (Macfarlane et al, 2004;Parsons et al, 2004;Forrest and Moore, 2008). Numerous studies report the biomass yield of these species as shortrotation crops established at various stockings (Barton and Montagu, 2006;Sochacki et al, 2007;Forrest and Moore, 2008).…”
Section: Introductionmentioning
confidence: 99%